Assessment of the digital transformation impact on the structural changes dynamics in the Russian economy - Petrova Elena; Buyanova Marina; Kalinina Vera (E3S Web of Conferences, 2023)
The purpose of this study is a quantitative assessment of the structural changes dynamics; the authors propose to assess these shifts based on an analysis of changes occurring within the economy sectoral structure and the gross value added in recent years. Another purpose is to identify the relations between economic development and the digital technologies use in the Russian economy in general, which allow to evaluate the effectiveness of the strategy implementation as part of the development of the Digital Economy in the country in general. The Gatev’s coefficient is the most effective tool for calculating the magnitude of structural changes, it allows to evaluate the dynamics of changes, as well as to identify structural changes based on the effectiveness. The empirical base of the study consists of statistical materials on the gross value added reflected in the industry structure, statistical publications on the use of various types of digital technologies and on digital technology expenses from 2005 to 2022. The study identified the trends of the Gatev’s structural changes coefficients dynamics and provided their quantitative assessment according to the selected indicators for Russia. An analysis of the comparability of economical structural changes both in terms of the use and the costs of digital technologies was carried out. The obtained results of the quantitative assessment served as the basis for substantiating the identified dynamics for the quantitative assessment of the structural changes taking place in the country's economy and the dynamics of the use of digital technologies.